Analisis Kelas Virtual Google Classroom Pada Pelatihan TIK Bagi Guru Madrasah Tsanawiyah Di Wilayah Kerja Kantor Kementerian Agama Kabupaten Labuhan Batu Selatan - Gunarno Gunarno (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2021)
Google Classroom Virtual Class Analysis on Information and Communication Technology (ICT) Training for Madrasah Tsanawiyah Teachers in the Work Area of ​​the Ministry of Religion, South Labuhan Batu Regency. This study aims to determine the description of the virtual google classroom that has been created by the trainee teachers in ICT Training for Madrasah Tsanawiyah Teachers in the Work Area of ​​the Ministry of Religion, Labuhan Batu Selatan Regency. The research subjects were participants in the ICT Training for Madrasah Tsanawiyah Teachers in the Work Area of ​​the Ministry of Religion, Labuhan Batu Selatan Regency, which was held from 11 until 16 January 2021 totaled 30 people, with 2 aspects observed, namely the general aspect and the accessibility aspect. This research method is descriptive research. Data was obtained through observation and then analyzed using mean analysis. The results of data analysis showed that 46.67% of the training participants had an eligibility value of the Google Classroom virtual class with the "Very Eligible" category, 53.33% of the training participants had a feasibility value in the "Eligible" category.